Persepsi Permeabilitas Kota Singaraja Menurut Generasi Milenial - Prita Ayuningtyas; Nyoman Susanta; Ni Made Yudantini (Jurnal Arsitektur ARCADE, 2025)
Abstract: Singaraja City, the capital of Buleleng Regency, plays a strategic role in the historical and spatial development of North Bali. However, the city is currently facing challenges related to accessibility and spatial connectivity, particularly in areas with aging road networks and suboptimal pedestrian infrastructure. These issues reflect a low level of urban permeability, defined as the degree to which urban spaces allow free movement and functional connectivity. This study aims to explore the perceptions of the Millennial Generation toward the level of permeability in Singaraja City, focusing specifically on the Udayana Street corridor, which functions as a hub for education and daily urban mobility. Using a qualitative approach that combines field observation, in-depth interviews, and mental mapping, the study investigates accessibility quality, mobility constraints, and spatial connectivity as experienced by young adults (born 1994–2000). The findings reveal that Millennials are highly aware of the physical conditions of urban spaces, such as the lack of continuous pedestrian paths, poor street lighting, and spatial disconnection across neighborhoods. Although Udayana Street holds a strategic urban function, it is not yet fully supportive of active mobility. This study contributes to the theoretical understanding of urban permeability in medium-sized cities and provides valuable input for urban planners and policymakers to develop inclusive, youth-responsive, and sustainable mobility strategies. Keywords: Urban Permeability, Milennial Generation, Singaraja City Abstrak: Kota Singaraja sebagai ibu kota Kabupaten Buleleng memiliki peran strategis dalam sejarah dan dinamika pembangunan wilayah Bali Utara. Namun, perkembangan kota ini menghadapi tantangan dalam hal aksesibilitas dan keterhubungan ruang, terutama di kawasan dengan jaringan jalan lama dan infrastruktur pejalan kaki yang belum optimal. Permasalahan ini mencerminkan rendahnya tingkat permeabilitas kota, yaitu sejauh mana ruang kota memungkinkan pergerakan bebas dan konektivitas antarfungsi ruang. Penelitian ini bertujuan untuk mengkaji persepsi Generasi Milenial terhadap tingkat permeabilitas Kota Singaraja, khususnya di koridor Jalan Udayana yang menjadi pusat aktivitas pendidikan dan mobilitas harian. Dengan menggunakan pendekatan kualitatif melalui observasi, wawancara mendalam, dan peta mental, penelitian ini menganalisis kualitas aksesibilitas, hambatan mobilitas, dan keterhubungan antar ruang berdasarkan pengalaman generasi muda usia produktif (lahir 1994–2000). Hasil penelitian menunjukkan bahwa Generasi Milenial memiliki kepekaan terhadap kondisi fisik ruang kota, seperti keterbatasan jalur pejalan kaki, kurangnya penerangan jalan, hingga kesenjangan konektivitas antar kawasan. Kawasan Jalan Udayana dinilai memiliki fungsi strategis, namun belum sepenuhnya ramah terhadap mobilitas aktif. Penelitian ini memberikan kontribusi terhadap pemahaman konsep permeabilitas kota dalam konteks kota sedang, serta menjadi masukan penting bagi perencana kota dan pemangku kebijakan dalam merumuskan kebijakan ruang yang inklusif, responsif terhadap kebutuhan generasi muda, dan mendukung mobilitas berkelanjutan. Kata Kunci: Permeabilitas kota, Generasi Milenial, Kota Singaraja Keywords: Urban Permeability, Milennial Generation, Singaraja City